Ecopreneurship Sebagai Strategi Inovatif Pengembangan UMKM di Kabupaten Ponorogo dalam Perspektif Maqāṣid Asy-Syarī‘ah - Evin Isnaini; Candra Febrilyantri (Niqosiya: Journal of Economics and Business Research, 2025)
Ecopreneurship focuses on environmental sustainability and plays a strategic role in local economic growth as well as being an innovative solution for Ponorogo MSMEs to overcome the waste problem. This concept is in line with Maqāṣid Asy-syarī'ah principles that emphasize protection and sustainable business practices. The method used in this research is qualitative method. Data collection techniques were carried out through observation, interviews, and documentation of ecopreneurship MSME owners in Ponorogo. The results showed that ecopreneurship in Ponorogo is run in line with the principles of eco-innovation, eco-opportunity, and eco-commitment. In its development, ecopreneurship MSMEs in Ponorogo are still constrained by capital issues. The development of these MSMEs is supported by the principles of Maqāṣid Ash-sharī'ah through business ethics, work safety, knowledge enhancement, moral preservation, and the balance of profit and social responsibility for business sustainability. Ecopreneurship has proven to be an innovative strategy in the development of MSMEs in Ponorogo Regency. This strategy not only encourages economic growth and competitiveness of MSMEs, but also aligns with the principles of Maqāṣid Asy-syarī'ah.